Penerapan Jaringan Syaraf Tiruan Deteksi Bahaya Kelebihan Mengkomsumsi Kafein dengan Menggunakan Metode Backpropagation - Lidia Sinurat (Journal of Information System Research (JOSH), 2020)
Artificial Neural Network (ANN) is one of the artificial representations of the human brain that always tries to simulate the learning process of the human brain. Backpropagation training algorithm or can be translated into back propagation, first formulated by Werbos and popularized by Rumelhart and McCelland to be used in ANN, and then this algorithm is usually appointed as BP. This algorithm includes a supervised training method and design for operations on multi-layer feed forward networks. Caffeine is an alkaloid found in various types of plants, especially coffee plants, colas, tea and so forth. Caffeine functions as a stimulant for the central nervous system, aphrodisiacs and can ward off katuk and restore alertness. But the side effects, caffeine has the potential to cause mutations of chromosomes that are mutagenic